Murihiku Cultural Water Classification System: enduring partnerships between people, disciplines and knowledge systems. Issue 4 (2nd October 2018) - Kitson, Jane C.; Cain, Ailsa M.; Johnstone, Muriel N. Te Huikau; Anglem, Rewi; Davis, Jane; Grey, Moana; Kaio, Aimee; Blair, Stevie-Rae; Whaanga, Dean
ABSTRACT: The Murihiku Cultural Water Classification System is founded on partnerships between people, disciplines and knowledge systems. This freshwater management framework is being developed at the scale of the Te Ara Koroka Pounamu Trail. Numerous barriers prevented Ngāi Tahu ki Murihiku use of the trail from around the 1880s; however, this cultural landscape and the values, beliefs and practices it supports (past, present and future) are still central to the identity of Murihiku whānau. To help reconstruct and revitalise mātauranga Māori around Te Ara Koroka, historical literature sources were used, alongside cultural value mapping, interviews and contemporary information sources. This paper explores cultural heritage methods to show how indigenous knowledge can be meaningfully and respectfully protected in research programmes. We propose that access requirements and protection mechanisms used by museums, libraries and archives could inform improved processes to better protect mātauranga Māori within the New Zealand science and innovation system.